Innovative Farming Practises in Sahel - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
In late September, The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) West Africa program team, together with partner the Institute of Environment and Agricultural Research (INERA) visited the District of Zandoma, in Burkina Faso. The main objective of the field visit was to interview key members of the Association of Innovative Farmers of Zandoma, and especially its President, Boureima Ouedraogo. They have experience from integrating agricultural practices that have enhanced resilience in their community and on their farms, in the Sahel.